Parasitic diseases and academic performance of schoolchildren - Epstein, Erwin H.
This paper considers the effect of parasitic disease, especially bilharzia, on students' performance in schools across St. Lucia, and seeks to account for the effects of socio-economic and urban-rural differences, and habits and knowledge in regard to disease. The sample consisted of 162 students from 37 primary schools and 8 secondary schools in almost every community in the island. The results revealed little evidence that bilharzia or other parasitic diseases in St. Lucia exert important effects on the performance of students as measured by reading achievement level or class rank. Neither was there evidence that these diseases adversely affect students' height, weight, or school attendance. On the other hand, socio-economic status did appear to have an important impact on performance, with children of fathers with high-status occupations generally recording higher on tests. Overall, the findings appear to indicate that when social background factors are considered together with parasitic diseases in areas of high disease prevalence, the social factors might well eclipse disease in influencing the performance levels of students
Keywords: Academic achievement